Clinical outcomes of single-dose cardioplegia in high-risk coronary bypass. (February 2021) - Gunaydin, Serdar; Gunertem, Orhan Eren; Babaroglu, Seyhan; Kunt, Atike Tekeli; McCusker, Kevin; Ozisik, Kanat
Background: Despite the increasing popularity of single-dose cardioplegia techniques in coronary artery bypass grafting, the time window for successful reperfusion remains unclear. This study aimed to compare different cardioplegic techniques based on early and 30-day clinical outcomes via thorough monitoring. Methods: This prospective cohort study included high-risk patients undergoing coronary artery bypass grafting and receiving 3 different types of cardioplegia between January 2017 and June 2019. Group 1 ( n  = 101) had a single dose of del Nido cardioplegia, group 2 ( n  = 92) had a single dose of histidine-tryptophane-ketoglutarate, and group 3 ( n  = 119) had cold blood cardioplegia. Patients were examined perioperatively by memory loop recording and auto-triggered memory loop recording for 30 days, with documentation of predefined events. Results: Interleukin-6 and cardiac troponin levels in group 1 were significantly higher than those in groups 2 and 3. The incidence of predefined events as markers of inadequate myocardial protection was significantly higher group 1, with more frequent atrial fibrillation attacks and more hospital readmissions. The readmission rate was 17.6% in group 1, 9% in group 2, and 8% in group 3. Conclusions: Our data demonstrate the long-term efficacy of cardioplegic techniques, which may become more crucial in high-risk patients who genuinely have a chance to benefit from adjunct myocardial protection. Patients given del Nido cardioplegia had a significantly more prominent inflammatory response and higher troponin levels after cardiopulmonary bypass. This group had issues in the longer term with significantly more cardiac events and a higher rehospitalization rate.